2011
DOI: 10.1002/dmrr.1264
|View full text |Cite
|
Sign up to set email alerts
|

Killer cell immunoglobulin‐like receptor along with HLA‐C ligand genes are associated with type 1 diabetes in Chinese Han population

Abstract: In our study of a Han population (East China), we found no direct association of KIR genes with T1D. However, a combination of HLA-C1 and -C2 showed a positive association with T1D. Different combinations of HLA-C and KIR showed positive and negative association with T1D.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 61 publications
(56 reference statements)
1
31
0
Order By: Relevance
“…A study of a Hunan Han Chinese population revealed significant findings with 2DL1, 3DL1 and 2DS4 . Interestingly, another study also performed on Chinese Han patients showed no significant associations between KIR genes and Type 1 diabetes . This is similar to a Japanese study, which also showed no significant associations between KIR genes and Type 1 diabetes .…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…A study of a Hunan Han Chinese population revealed significant findings with 2DL1, 3DL1 and 2DS4 . Interestingly, another study also performed on Chinese Han patients showed no significant associations between KIR genes and Type 1 diabetes . This is similar to a Japanese study, which also showed no significant associations between KIR genes and Type 1 diabetes .…”
Section: Discussionsupporting
confidence: 81%
“…Interestingly, even Japanese and Han Chinese populations showed these associations with disease, even though their individual KIR genes were not significant for Type 1 diabetes. Both studies published on Chinese Han populations showed that 2DS1−/HLA–C2− is negatively associated with Type 1 diabetes .…”
Section: Discussionmentioning
confidence: 99%
“…The combinations of KIR variants and specific variants of the cognate HLA ligands should be analyzed in future studies to refine the analysis in search of signatures of natural selection. Several examples of associations between KIR / HLA genotypes and variation of susceptibility to multifactorial diseases have been reported [37][41]. Some of these combined genotypes affect morbidity and mortality and thus fitness, therefore signs of natural selection could be revealed at the levels of both population and nucleotide/aminoacid sequence analyses, as reported for the KIR3DL1/S1 polymorphism [42].…”
Section: Discussionmentioning
confidence: 92%
“…KIR allelic products have been shown to differ in their specificity and affinity regarding ligand binding [13], and these allelic differences may contribute to disease susceptibility and progression [14]. The frequencies of KIR genes and haplotypes show great variation among different populations, and the crucial function of KIRs in immunity may have an impact on susceptibility to infection, autoimmune diseases and transplantation outcomes among different ethnic groups [10,15,16].…”
Section: Introductionmentioning
confidence: 99%